Effects of Online Learning and Students Psychomotoric Changes in Writing Short Stories - Erfinawati, (Jurnal Serambi Ilmu, 2024)
The purpose of this study was to know the effect of online learning on students' psychomotor changes in writing short stories (Cerpen). The data sources in this study were students of SMPN 4 and SMPN 9 Banda Aceh. The method used is descriptive qualitative and quantitative. Data collection techniques in this study are test, observation, interview and documentation techniques.The data processing technique was carried out using the SPSS program. The results showed that online learning at SMPN 4 Banda Aceh had no significant effect on psychomotor changes in writing short stories. While the results of research at SMPN 9 Banda Aceh showed that online learning had a significant effect on psychomotor changes in students' short stories writing. The results of the interview show that online learning has positive and negative effects depending on the learning pattern.